Interactions of copper, selenium, and vitamin E for weanling swine - A J Thulin; D S Pollmann; Frank Blecha; G A Kennedy; P Whetter; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1984)
One-hundred and sixty pigs were utilized to evaluate possible interactions between copper (Cu), selenium (Se), and vitamin E (E) on growth and immunity of starter pigs. Copper (260 ppm) added to the diet did not effect Se and/or E utilization for growth, feed efficiency (FE), or immunity. However, addition of 260 ppm of Cu to the diets of starter pigs resulted in an 8% improvement in feed intake (FI) and a 13% improvement in average daily gain (ADG) for the first 2 wk on test. There was no effect on performance due to E additions. However, addition of .3 ppm Se to the diets resulted in an overall 5% improvement in FE and a 7% improvement in ADG. Additions of dietary Cu, Se and E had no effect on immunity and no evidence of tissue lesions or symptoms typical of Se and E deficiency were found.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Copper; Selenium; Vitamin E; Weanling